[Football Squad in uniform] - Frank Aston::::::photographer::: (1915)
Group portrait of football team in uniform, with coach D.W. Schlosser; seated on steps; pennants held by students in front row. Photo of same team (different pose) was published in the Polytechnic J. (v.11, no.1, June 1916) with caption identifying the members. Also in Cal Poly. Bulletin (1916-17).